Using the Quizizz Application for Faith in Angels Allah For Improving Student Learning Outcomes in The Eyes Islamic Religious Education Lessons During the Covid-19 Pandemic : Penggunaan Aplikasi Quizizz Materi Beriman Kepada Malaikat Allah Untuk Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di Masa Pandemi Covid-19 - Siti Rahmatul Fitriyah; Eni Fariyatul Fahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the level of effectiveness of using Quizizz media on the academic value of students at SDN Entalsewu class IV Sidoarjo city. The research was conducted using a quantitative approach with a hypothesis testing method. Homogeneity test and normality test were carried out first. Homogeneity and normality tests were used to determine the level of normality of the data and the distribution of values ​​in the analyzed data. The subjects in this study were 62 fourth grade students at SDN Entalsewu Sidoarjo who had difficulty focusing on doing exercises on PAI Subjects. Data was collected using the Pretest and Posttest tests. Based on the results of the study, there was an increase in PAI learning achievement related to the material of the pillars of faith. This can be seen in the results of the data analysis test using the Paired sample t-test which shows a Sig (2-tailed) value of 0.000. This shows Sig(2-tailed) < 0.05, which means H0 is rejected and Ha is accepted. In other words, the use of the Quizizz application in PAI learning is effective in improving the achievement results of fourth grade students at SDN Entalsewu Sidoarjo.